2011
DOI: 10.1007/s00606-011-0504-5
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the hybrid origin of the Chinese tea roses: evidence from DNA sequences of single-copy nuclear and chloroplast genes

Abstract: The tea-scented China roses largely correspond to the three recognized double-petaled Rosa odorata (Andrews) Sweet (Rosoideae, Rosaceae) varieties, which are the ancestors of modern hybrid tea roses and had a definite and permanent influence on the evolution of modern garden roses. Here the hypothesis of a hybrid origin of the tea-scented China roses between R. odorata var. gigantea and R. chinensis was tested. Two single-copy nuclear genes of the cytosolic glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 57 publications
3
33
0
Order By: Relevance
“…4 and 5). This relationship was also recovered in previous studies (Bruneau et al, 2007;Fougère-Danezan et al, 2015;Meng et al, 2011;Qiu et al, 2012;Wissemann and Ritz, 2005). Our phylogenies showed that these species together are not monophyletic, and chloroplast phylogeny resolved R. lucidissima as the earliest divergent species in the Asian subclade.…”
Section: Phylogeny Of Rosa Sections Chinenses and Synstylaesupporting
confidence: 87%
See 2 more Smart Citations
“…4 and 5). This relationship was also recovered in previous studies (Bruneau et al, 2007;Fougère-Danezan et al, 2015;Meng et al, 2011;Qiu et al, 2012;Wissemann and Ritz, 2005). Our phylogenies showed that these species together are not monophyletic, and chloroplast phylogeny resolved R. lucidissima as the earliest divergent species in the Asian subclade.…”
Section: Phylogeny Of Rosa Sections Chinenses and Synstylaesupporting
confidence: 87%
“…Chinenses and Synstylae. However, hybridization seems to be at work in these two sections as suggested by previous studies (Ohba et al, 2000;Meng et al, 2011) and numerous intermediate morphological characters from specimens and field observations.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…spontanea and R . x odorata var gigantea [6], consistent with the relatively low sequence divergence of R. chinensis var. spontanea compared to the HapOB reference sequence.…”
Section: Resultsmentioning
confidence: 56%
“…Roses present an ideal model for woody and ornamental plants, but also display a range of unique features thanks to their complex evolutionary history including interspecific hybridization events and polyploidisation [46]. Roses belong to the genus Rosa (Rosoideae, Rosaceae) , which contains more than 150 species [7] with varying levels of ploidy, ranging from 2n=2× to 10× [8, 9].…”
Section: Introductionmentioning
confidence: 99%